Peran Body Shaming Terhadap Kesehatan Mental - Veronika Halla; Fredericksen Amseke (Ra'ah: Journal of Pastoral Counseling, 2025)
Body shaming in teenagers causes mental health problems so that teenagers feel they are imperfect, unable to solve their problems and lack self-confidence. The aim of this research was to examine the effect of body shaming on adolescent mental health among students in the pastoral counseling study program at Institut Agama Kristen Negeri Kupang. This research uses quantitative methods. Data collection tools use a body shaming scale and a mental health scale. The respondents in this study were 54 young students in the pastoral counseling study program at Institut Agama Kristen Negeri Kupang. The data analysis technique uses simple linear regression analysis. The results of this study prove that there is a positive and significant influence of body shaming on the mental health of adolescent students with an F value = 26.049 and a p value = 0.000 at R Square = 0.216. The effective contribution of the body shaming variable to mental health is 33.4%, meaning that body shaming can affect the mental health of teenagers in students of the pastoral counseling study program at Institut Agama Kristen Negeri Kupang.